Genetic architecture of plant stress resistance: multi‐trait genome‐wide association mapping. Issue 3 (4th October 2016) - Thoen, Manus P. M.; Davila Olivas, Nelson H.; Kloth, Karen J.; Coolen, Silvia; Huang, Ping‐Ping; Aarts, Mark G. M.; Bac‐Molenaar, Johanna A.; Bakker, Jaap; Bouwmeester, Harro J.; Broekgaarden, Colette; Bucher, Johan; Busscher‐Lange, Jacqueline; et al.
Summary: Plants are exposed to combinations of various biotic and abiotic stresses, but stress responses are usually investigated for single stresses only. Here, we investigated the genetic architecture underlying plant responses to 11 single stresses and several of their combinations by phenotyping 350 Arabidopsis thaliana accessions. A set of 214 000 single nucleotide polymorphisms (SNPs) was screened for marker‐trait associations in genome‐wide association (GWA) analyses using tailored multi‐trait mixed models. Stress responses that share phytohormonal signaling pathways also share genetic architecture underlying these responses. After removing the effects of general robustness, for the 30 most significant SNPs, average quantitative trait locus (QTL) effect sizes were larger for dual stresses than for single stresses. Plants appear to deploy broad‐spectrum defensive mechanisms influencing multiple traits in response to combined stresses. Association analyses identified QTLs with contrasting and with similar responses to biotic vs abiotic stresses, and below‐ground vs above‐ground stresses. Our approach allowed for an unprecedented comprehensive genetic analysis of how plants deal with a wide spectrum of stress conditions.